THE COVID-19 AND MALAYSIA ECONOMY : A BIBLIOMETRIC ANALYSIS - Abdul Hayy Haziq, Mohamad; MUHAMAD RIAS K, V ZAINUDDIN; MOHD SUFIAN, MOHAMED ESA; Rossazana, Ab Rahim (UMT Press, 2024)
The COVID-19 pandemic is a serious issue that has been classified as a global issue. There are millions of people reported to have died after being infected with the COVID-19 epidemic. This caused the Malaysian government to create a Movement Control Order (MCO) to prevent the spread of the COVID-19 epidemic. However, this has a negative impact on the economy in Malaysia. This bibliometric study uses the keywords “COVID-19”, “economy”, and “Malaysia” to analyse previous studies that discuss issues related to these keywords. The Scopus database served as the source of the information used in this study’s bibliometric analysis. The study can gather 511 papers to analyse the publication year, document type, source title, languages, subject area, keyword analysis, authorship, active institutions, and citation analysis. These are some common bibliometric indicators used in this study to provide the findings. For the frequency study, Microsoft Excel was used; VOSviewer was used for data visualisation; and Harzing’s Publish or Perish was used for citation metrics and analysis. The study is strongly related to the top author’s keywords, as COVID-19 is recorded to have 45.79%, and the Malaysia keyword is 40.90%. Most documents are the qualities Scopus articles, with the majority of articles with 348 total publications (68.10%), conference papers with 71 total publications (13.89%), book chapters with 51 total publications (9.98%), and review papers with 28 total publications. The article “The Use of the Health Belief Model to Assess Predictors of Intent to Receive the COVID-19 Vaccine and Willingness to Pay” by Wong et al. (2020) has received the most citations so far, with 513 citations, or an average of 171 citations per year.